2014
DOI: 10.4018/ijabim.2014040107
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study on China's Gold Futures Market Hedging Performance

Abstract: In the current financial crisis, promoting rapid developments of gold industry, ensuring healthy operations of national economy, and actively developing the gold futures market are very important. Functioning of the gold futures market will determine the gold market maturity and integrity. Risk transfer is one of the two basic functions of futures market. The risk transfer function is realized through hedging. China's gold futures market has been in market for more than four years, is the risk transfer functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Wei studied the comovement of US dollar, oil futures and gold futures and concluded that the hedging effect of the combination of crude oil futures and gold futures on exchange rate risk is better than the traditional hedging strategy [4]. Zhu and Xu used the various hedging models to test the stationarity and cointegration relationship between the futures price and spot price data, finally found that the ECHM and EC-GARCH models provide better hedging results than the OLS and B-VAR models [5]. Zhang and Xue put forward the US dollar index and international gold price cooperation set of interest strategy and give the international gold futures price risk-free arbitrage range [6].…”
Section: Introductionmentioning
confidence: 99%
“…Wei studied the comovement of US dollar, oil futures and gold futures and concluded that the hedging effect of the combination of crude oil futures and gold futures on exchange rate risk is better than the traditional hedging strategy [4]. Zhu and Xu used the various hedging models to test the stationarity and cointegration relationship between the futures price and spot price data, finally found that the ECHM and EC-GARCH models provide better hedging results than the OLS and B-VAR models [5]. Zhang and Xue put forward the US dollar index and international gold price cooperation set of interest strategy and give the international gold futures price risk-free arbitrage range [6].…”
Section: Introductionmentioning
confidence: 99%